Pengaruh Kompetensi dan Kecerdasan Emosional Terhadap Kinerja Guru SMA Budi Mulia Karawang - Ningrum, Avisha Natania; Tuhagana, Aji; Apriani, Zenita (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Education aims to create an effective system so as to achieve good quality learning. Teacher performance is influenced by competence and emotional intelligence. Competency supports teaching effectiveness, while emotional intelligence helps manage emotions and build positive relationships. Both play a role in improving teacher performance and learning quality. This study aims to determine the influence of competence and emotional intelligence on teacher performance at Budi Mulia Karawang High School. This researcher used quantitative and verifiable descriptive methods with a total teacher population of 38 teachers. Data analysis was carried out using SPSS26 using multiple linear regression tool methods. The results of this study can be concluded that competence obtained an average score of 168 with the very good category, emotional intelligence with an average score of 169.9 with the very good category and an average performance of 167.7 with the very good category. Meanwhile, competence partially has a very significant effect on performance with a sig value. 0.015 < 0.05, Thcal value 2.568 > Ttable 2.030. Emotional intelligence partially has a very significant effect on the GIS value. 0.001 < 0.05, Thitung 3,469 > Ttable 2,030. Simultaneously, competence and emotional intelligence had a very significant effect with a value of 0.000 < 0.05 and Fcal 53.655 > 3.26. The results of the Determination Test showed that the R-value squared was 0.754, which means that the variables X1 and X2 together had an influence of 75.4% on the Y variable, while 24.6% were influenced by other factors outside of this study.